Relecture de vocabulaires d’architecture : apport de la complexité des représentations numériques dans la caractérisation de formes architecturales - David Lo Buglio (In Situ)
By articulating terminology, functional logics and geometrical logics, the semantics of an element can be considered as an architectural concept. In many ways, architectural semantics is one of the foundations of architectural theory, essential for understanding stylistic evolutions in time and space. At the crossroads of architectural theory, art history and even survey practices, architectural vocabularies offer efforts to provide semantic standardisation that might be revisited today, in the light of recent scientific advances in the field of the built heritage. This article aims to reconcile the cognitive issues specific to the semantic study of architectural elements and the exploitation of big data resulting from building digitisations. It is necessary to compare the geometrical characterisation of a corpus of elements (resulting from the examination of the geometrical similarities shared by this corpus) with the description given by four architectural vocabularies. The challenge is to observe the encounters, but also the points of tension between a semantics proposed by the history of art and a semantics resulting from fine geometrical observations. By highlighting the contradictions between the vocabularies themselves and the geometric model, this article discusses the contribution of methods of analysis coming from computer graphics for the development of architectural knowledge.